The Sage handbook of innovation in social research methods - Williams, Malcolm, Ed; Vogt, W Paul, Ed (Sage Publications, Inc., 2011)
"Social Research is a bourgeoning field. Of course it has many traditions and approaches, but there is a high premium upon thinking differently and thinking anew because social life is never static or wholly predictable. This Handbook, edited by internationally recognized scholars in the field, provides a comprehensive, pitch perfect critical assessment of the field. The main features of the Handbook are: Clear organization into 4 parts dealing with The Social Context of Research; Design and Data Collection; Integrating The Analysis of New Data Types; Sampling, Inference and Measurement ; Clear, cutting edge chapters on Objectivity; Effects; Organizing Social Research; Correspondence Analysis; Grounded Theory; Conversational Surveys; Mixed Methods; Regression Analysis; Optimal Matching Analysis; GIS Analysis; Quantitative Narrative Analysis; Longitudinal Studies; Equation Modeling ; Brings together a glittering assembly of the key figures working in the field of Methods today ; Demonstrates the continuities and productive tensions between classical traditions and real world research today. The result is a superbly organized text which will be required reading for anyone interested in the routes and future of social research. It is an unparalleled teaching resource and a 'must have' for serious social researchers."--Publisher's website.